EMERGING THREATS IN CYBERSECURITY: ANALYZING RANSOMWARE EVOLUTION (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2026)
Ransomware has evolved into one of the most pervasive and destructive threats in the field of cybersecurity, transitioning from basic malware targeting individuals to highly sophisticated attacks aimed at critical infrastructure and large organizations. This research explores the technological progression, strategic shifts, and monetization models driving the ransomware epidemic, with particular focus on the rise of Ransomware-as-a-Service (RaaS), advanced encryption techniques, and multi-layered extortion tactics. The study highlights the increasing accessibility of ransomware tools, the growing professionalism of cybercriminal groups, and the implications for cybersecurity preparedness and response. Findings indicate that combating ransomware requires a multifaceted approach involving technical innovation, user education, international cooperation, and legal reform. This paper contributes to a deeper understanding of ransomware’s evolution and offers insights into developing more resilient defenses against emerging cyber threats.